Gestión administrativa en la Empresa Avipaz Cia Ltda sucursal Montalvo - Espinoza Romero, Byron Javier (2021)
The present case study was carried out at Empresa Avipaz Cia Ltda, Montalvo branch, the subject of study is administrative management, which is one of the basic and elementary aspects in any type of organization. The objective of the research was to analyze the most important aspects of the administrative functioning of the aforementioned company to identify weaknesses that need to be improved, in such a way that the organization achieves more and better results. The methodological framework is composed of a qualitative design with a descriptive scope, where two types of research have been used: documentary and field; The method used is deductive through the interview as a research technique through which information was collected from primary sources. The conclusions reached in the study is that the company Avipaz Cia Ltda does not have effective administrative management, mainly due to the fact that the administrative process is not properly applied, an aspect that affects the motivation of employees , which in turn conditions their job performance. All these aspects limit the achievement of the company's objectives.